S100 Is it feasible to assess dynamic hyperinflation during an incremental treadmill test in patients with severe asthma?. (12th November 2015) - Majd, S; Dolmage, TE; Green, RH; Bradding, P; Singh, SJ; Evans, RA
Abstract : Introduction: We wish to investigate whether dynamic hyperinflation contributes to exercise intolerance in patients with severe asthma. It is unclear whether there is an influence by the exercise platform. To begin with, we explored whether performing serial inspiratory capacity (IC) manoeuvres is feasible during a maximal incremental treadmill test in patients with severe asthma. Method: Patients with severe asthma (step 4–5 of the British Thoracic Society guidelines), MRC dyspnoea grade ≥2, were recruited from physicians specialising in the care of patients with difficult-to-treat asthma at Glenfield Hospital, Leicester. Patients were excluded if they had both fixed airflow obstruction (FEV1 /FVC <70%) and a smoking history of ≥10 pack years. All participants performed an incremental treadmill test to intolerance, with expiratory gas analysis, designed to produce a linear increase in peak oxygen uptake (VO2 ). 1 Patients performed a practice resting inspiratory capacity manoeuvre and then subsequently at rest, during the warm up phase and every two minutes during exercise. Results: 18 participants (8 female, mean [SD] 49 [14] yrs, BMI 31 [7] kg/m 2, FEV1 /FVC 70 [13]%, 17% were ex-smokers) completed the treadmill test in a duration of 482 [120] s. Observations at peak exercise were: VO2 2.0 [0.4] L/min (100 [25]% predicted); ventilation 67 [18] L/min (87 [20]% maximum voluntary ventilation); heart rate 145 [17] beats/min (85 [9]% predicted); Borg Score for breathlessness 7 [2], perceived exertion 17 [3], 16 were predominantly limited by breathlessness. 115 IC manoeuvres were performed with only one datapoint missed due to an incomplete manoeuvre. Figure 1 shows the mean end expiratory and inspiratory lung volumes during exercise. Six patients had an inspiratory reserve volume of <500 mls. Conclusion: Assessment for dynamic hyperinflation with serial inspiratory capacity manoeuvres during a maximal incremental treadmill test is feasible in patients with severe asthma. The relationship among lung volumes, time and ventilation can be established from rest to peak exercise with minimal practice of the IC manoeuvre or interruption to the test in this patient population. Reference: 1 Porszasz J, Casaburi R, Somfay A, et al . Med Sci Sports Exerc . 2003;35 : 1596–1603